Clinical comparison of radiofrequency ablation and surgical resection in treating pulmonar metastasis of hepatoblastoma - Li, Yang; Niu, Hongxin; Xu, Huirong; Wang, Jian; Wang, Jingfu; Liu, Yizhi; Liu, Xuena (Frontiers in Oncology, 2025)
ObjectiveTo explore the efficacy variances between radiofrequency ablation and traditional surgical resection in treating pulmonary metastasis of hepatoblastoma in children, and to provide more feasible methods for the treatment of this disease.MethodsA total of 91 pediatric hepatoblastoma (HB) patients with pulmonary metastases, admitted to Shandong Cancer Hospital between Sept. 2021 and Oct. 2023, were enrolled in this study. Among them, 31 received radiofrequency ablation for pulmonary metastasis eradication, while 60 underwent surgical resection to remove the pulmonary metastases. To assess the comparative effectiveness of these two interventional approaches in treating pediatric pulmonary metastases from hepatoblastoma, differences between the two groups were analyzed in terms of alpha-fetoprotein (AFP) levels, complication rates, antibiotic use, operative duration, length of hospital stay, and hospitalization costs.ResultsThe average levels of AFP in both the radiofrequency ablation group and the surgical resection group decreased significantly after treatment, with no statistical significance between the groups (P>0.05). The incidences of pneumonia, pulmonary atelectasis, and pneumothorax were statistically different between the groups (P < 0.05). Antibiotic use was markedly lower in the radiofrequency ablation group (χ2 = 43.4291, P < 0.001) as was the usage of advanced antibiotics (χ2 = 56.3477, P < 0.001) compared to the surgical group. Additionally, both the operation time (t = 11.186, P < 0.001) and hospitalization duration (t = 6.064, P < 0.001) were significantly shorter in the radiofrequency ablation group. The treatment costs for the radiofrequency ablation group were also significantly lower than those for the surgical group (t = 3.092, P = 0.003).ConclusionRadiofrequency ablation for HB pulmonary metastases is more feasible, safer, and cost-effective due to its advantages of less invasive and painful, faster recovery, economical, and lower adjacent complication rate.